Electron transfer dissociation provides higher‐order structural information of native and partially unfolded protein complexes. Issue 16 (22nd July 2015) - Lermyte, Frederik; Sobott, Frank; Barran, Perdita; Cooper, Helen; Eyers, Claire
<x xml:space="preserve">Abstract</x> Top–down sequencing approaches are becoming ever more popular for protein characterization, due to the ability to distinguish and characterize different protein isoforms. Under non‐denaturing conditions, electron transfer dissociation (ETD) can furthermore provide important information on the exposed surface of proteins or complexes, thereby contributing to the characterization of their higher‐order structure. Here, we investigate this approach using top–down ETD of tetrameric hemoglobin, concanavalin A, and alcohol dehydrogenase combined with ion mobility (IM) on a commercially available quadrupole/ion mobility/time‐of‐flight instrument (Waters Synapt G2). By applying supplemental activation in the transfer cell (post‐IM), we release ETD fragments and attain good sequence coverage in the exposed terminal regions of the protein. We investigate the correlation between observed sites of fragmentation with regions of solvent accessibility, as derived from the crystal structure. Ion acceleration prior to ETD is also used to cause collision‐induced unfolding (CIU) of the complexes without monomer ejection, as evidenced by the IM profiles. These partially unfolded tetramers show efficient fragmentation in some regions which are not sequenced under more gentle MS conditions. We show that by increasing CIU in small increments and monitoring the changes in the fragmentation pattern, it is possible to follow the initial steps of gas‐phase protein unfolding. Fragments from partially unfolded protein complexes are released immediately after electron transfer, prior to IM (they do not share the drift time of their precursor), and observed without the need for supplemental activation. This is further evidence that the higher‐order structure in these protein regions has been disrupted.